2013
DOI: 10.19030/jier.v9i4.8266
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Self Efficacy: Is Reporting Non-Significant Results Essential?

Abstract: Self

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Teachers at the age of 48-60 years could experience a decrease in enthusiasm for work due to boredom. It is consistent with several studies that have been conducted, which disclosed that a long working period (more than 24 years) tended to result in a decrease in learning motivation because teachers tended to experience boredom [38], [39]. Teacher enthusiasm will decline with advancing age, which may be due to the boredom of teaching the same content for several years [32].…”
Section: Biology Teachers' Understanding Of the Argument-driven Inquiry And Think Pair Share Learning Model Based On Teachers' Experiencesupporting
confidence: 90%
“…Teachers at the age of 48-60 years could experience a decrease in enthusiasm for work due to boredom. It is consistent with several studies that have been conducted, which disclosed that a long working period (more than 24 years) tended to result in a decrease in learning motivation because teachers tended to experience boredom [38], [39]. Teacher enthusiasm will decline with advancing age, which may be due to the boredom of teaching the same content for several years [32].…”
Section: Biology Teachers' Understanding Of the Argument-driven Inquiry And Think Pair Share Learning Model Based On Teachers' Experiencesupporting
confidence: 90%
“…While some studies claimed no significant outcomes, most studies showed significant positive outcomes of DST which could be explained by the novelty effect of technology and the drawer effect which refers to the tendency to publish significant results (Wu & Chen, 2020). On the other hand, reporting statistically nonsignificant results are important to direct teachers and researchers (Moalosi, 2013); therefore, this study aimed to highlight the DST process of undergraduate students including the application of creativity scale and the Targeting Creativity Through A Learner-Generated Digital Storytelling Project. conduct of detailed observation.…”
Section: Discussionmentioning
confidence: 99%